2018
DOI: 10.1200/jco.2018.36.7_suppl.153
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of anxiety and depression in chronic lymphocytic leukemia (CLL) survivors.

Abstract: 153 Background: CLL is an indolent lymphoma effecting aging populations. Early stage patients are assigned to active surveillance and only 10% of patients require treatment at diagnosis. Active surveillance for CLL may increase susceptibility to anxiety and depression, resulting in enhanced comorbidities and reduced quality of life. However, little is known about the prevalence and risk factors of anxiety and depression in CLL. Methods: 125 CLL patients that were treatment naïve (n = 86) or previously chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The finding that both patients that are actively treated and those who first follow a watchful waiting approach until their disease progresses experience symptom burden, worries and anxiety from the disease itself is in line with the literature 2,14,48,49 . HRQoL is therefore critically important for the entire CLL population and should be thought of as a major goal of treatment and disease management as also highlighted by an international expert commission in haematological malignancies 21 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The finding that both patients that are actively treated and those who first follow a watchful waiting approach until their disease progresses experience symptom burden, worries and anxiety from the disease itself is in line with the literature 2,14,48,49 . HRQoL is therefore critically important for the entire CLL population and should be thought of as a major goal of treatment and disease management as also highlighted by an international expert commission in haematological malignancies 21 .…”
Section: Discussionmentioning
confidence: 59%
“…The finding that both patients that are actively treated and those who first follow a watchful waiting approach until their disease progresses experience symptom burden, worries and anxiety from the disease itself is in line with the literature. 2,14,48,49 HRQoL is therefore critically important for the entire CLL population and should be thought of as a major goal of treatment and disease management as also highlighted by an international expert commission in haematological malignancies. 21 As the QLQ-CLL17 taps into disease-related, and treatment-related CLL symptoms, using the questionnaire in daily clinical practice can help clinicians identify specific CLL symptoms that require further examination and discussion with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The initial screening retrieved 9426 citations, and following the data-extraction process, 12 primary studies (reported in 17 publications) were included in the HRQoL burden review (Figure 1). The 12 studies differed in terms of design, study populations, and the instruments used to measure HRQoL burden (Table 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . The majority of studies were conducted in the United States (n ¼ 6) and Europe (n ¼ 3); study populations included both treated and untreated patients, as well as those with R/R disease.…”
Section: Hrqol Burden Of Cllmentioning
confidence: 99%
“…Across studies included in the review, the mean age of patients with CLL ranged from 59-70 years [15][16][17][18]21,23,[26][27][28][29] and the proportion of male patients varied from 46% to 70% 15,17,21,23,[26][27][28] . Four primary studies investigated the impact of gender 15,16,21,26 and four investigated the impact of age 15,16,21,24 on HRQoL in patients with CLL.…”
Section: Impact Of Gender Age and Disease Stage On Hrqolmentioning
confidence: 99%